1999
DOI: 10.1111/j.1600-0846.1999.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cheek and forehead regions by bioengineering methods in women with different self‐reported “cosmetic skin types”

Abstract: Background/aims: Understanding structural and functional differences between facial areas is necessary for the formulation of cosmetics and dermatological preparations well tailored to the skin's biophysical characteristics. The objective of the present study was to compare biophysical parameters on malar and frontal facial areas of healthy women classified according to self‐reported cosmetic skin types. Methods: The study population comprised 253 women aged from 20 to 50 years who did not display any signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 21 publications
6
27
1
Order By: Relevance
“…There is little consensus within the scientific community on skin-type definitions [33], but the combination skin type seems to be most common [34,35]. Women with oily skin are prone to negative perception of their skin type [36] but demonstrate better judgement in its evaluation [37].…”
Section: Premenstrual Acne In Adult Womenmentioning
confidence: 99%
“…There is little consensus within the scientific community on skin-type definitions [33], but the combination skin type seems to be most common [34,35]. Women with oily skin are prone to negative perception of their skin type [36] but demonstrate better judgement in its evaluation [37].…”
Section: Premenstrual Acne In Adult Womenmentioning
confidence: 99%
“…However, a larger quantity of sebum was observed in greasy and combined skin types than the others, which implies the significance of sebum production in the determination of the cosmetic skin type (Fur et al, 1999;Kumagai et al, 1985). In addition, dryness of the skin was confirmed to be unrelated to the quantity of skin surface lipids (Fur et al, 1999;Pierard, 1987;Rurangirwa et al, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…However, a larger quantity of sebum was observed in greasy and combined skin types than the others, which implies the significance of sebum production in the determination of the cosmetic skin type (Fur et al, 1999;Kumagai et al, 1985). In addition, dryness of the skin was confirmed to be unrelated to the quantity of skin surface lipids (Fur et al, 1999;Pierard, 1987;Rurangirwa et al, 1987). Skin melanin, hemoglobin, and light scattering properties were quantitatively analyzed, and it was found that melanin is a major factor for the assessment of a particular type of skin, while the scattering properties provide information about the skin structure and morphology (Zonios et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations